2021
DOI: 10.1007/s11538-021-00890-8
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Specific Modelling of Blood Coagulation

Abstract: Blood coagulation represents one of the most studied processes in biomedical modelling. However, clinical applications of this modelling remain limited because of the complexity of this process and because of large inter-patient variation of the concentrations of blood factors, kinetic constants and physiological conditions. Determination of some of these patients-specific parameters is experimentally possible, but it would be related to excessive time and material costs impossible in clinical practice. We pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 49 publications
0
11
0
1
Order By: Relevance
“…Development of novel OAC's can be challenging and expensive, however, modelling tools 10.3389/fcvm.2022.1074562 are often employed in the early stages of pharmacological studies using RDC equations (75). Studies have investigated the patientspecific effects of warfarin and heparin on coagulation mechanisms, providing the scope for these tools to be extended to the most recent range of OACs, and development of new drugs for AF patients (93). The choice of whether to cardiovert is based on detection of an LAA thrombus, which can possibly be predicted using the modelling techniques outlined in this Review and ultimately identified by means of routinely available imaging techniques such as TEE.…”
Section: In-silico Stroke Preventionmentioning
confidence: 99%
“…Development of novel OAC's can be challenging and expensive, however, modelling tools 10.3389/fcvm.2022.1074562 are often employed in the early stages of pharmacological studies using RDC equations (75). Studies have investigated the patientspecific effects of warfarin and heparin on coagulation mechanisms, providing the scope for these tools to be extended to the most recent range of OACs, and development of new drugs for AF patients (93). The choice of whether to cardiovert is based on detection of an LAA thrombus, which can possibly be predicted using the modelling techniques outlined in this Review and ultimately identified by means of routinely available imaging techniques such as TEE.…”
Section: In-silico Stroke Preventionmentioning
confidence: 99%
“…Clot growth, that is, the spatial progression of the region filled by fibrin polymer gel, corresponds to the propagation of a reaction-diffusion wave [16]. A simplified model of blood coagulation consisting of three equations for the concentrations of prothrombin, thrombin and activated factor X was developed in [17] with patient-specific parameters. These results are used in the present work to determine the parameters of the one-equation model for the timedependent thrombin concentration T:…”
Section: The Model Of Clot Growthmentioning
confidence: 99%
“…and the values of parameters adjusted to [17] corresponding to the normal level of blood coagulation (Table 1). Calculations of the one-equation model with these parameters without blood flow gives the wave speed of thrombin propagation 0.54 micron/sec corresponding to the physiological range.…”
Section: The Model Of Clot Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed out by Chelle et al [14], most of the existing computational models fail to reproduce the thrombin formation dynamics in clinical settings without prior parameter optimization. To avoid this issue, some authors have suggested that instead of trying to find a universal set of reactions, reduced coagulation models are enough to reproduce the coagulation dynamics [9,15,16]. Nevertheless, a prior calibration step is still needed.…”
Section: Introductionmentioning
confidence: 99%